Osthole Regulates Secretion of Pro-Inflammatory Cytokines and Expression of TLR2 and NF-κB in Normal Human Keratinocytes and Fibroblasts - Kordulewska N; Topa J; Cieślińska A; Jarmołowska B (Dove Medical Press, 2022)
Natalia Kordulewska,1 Justyna Topa,2 Anna Cieślińska,1 Beata Jarmołowska1 1Department of Biochemistry, Faculty of Biology and Biotechnology, University of Warmia and Mazury, Olsztyn, Poland; 2Laboratory of Translational Oncology, Intercollegiate Faculty of Biotechnology, Medical University of Gdańsk, Gdańsk, PolandCorrespondence: Natalia Kordulewska, Tel + 48 89 523 37 63, Fax + 48 89 535 20 15, Email natalia.smulska@uwm.edu.plIntroduction: Osthole (OST), an active compound isolated from Cnidium monnieri, is used in traditional Chinese medicine to treat a variety of human diseases. Although OST has a good therapeutic effect, the underlying mechanism of its action in inflammatory skin diseases in humans is still unknown.Purpose: The present study aimed to test the hypothesis that OST can be used as an herbal substance that minimizes skin inflammation and barrier dysfunction. In this study, histamine and LPS were used to induce inflammation in skin keratinocytes and fibroblasts to test whether OST can inhibit their responses.Methods: Cell migration was analyzed using a wound healing assay. Changes in cell monolayer integrity were assessed by the measurement of transepithelial electrical resistance. Secretion of IL-1β, IL-6, IL-8, TNF-α, CCL2/MCP-1, CCL5/RANTES, and COX-2 was measured by ELISA, while expression of TLR2, NF-κB, and COX-2 was analyzed by qPCR.Results: OST decreased the level of IL-1β, TNF-α, CCL2/MCP-1 and CCL5/RANTES, and expression of TLR2, NF-κB and COX-2 during histamine/LPS-induced inflammation in human keratinocytes and fibroblasts. OST also improved cell migration and cell barrier function.Conclusion: Our results suggest that OST suppresses inflammatory responses via regulation of IL-1β, TNF-α, CCL2/MCP-1 and CCL5/RANTES secretion, and TLR2, and COX-2 expression.Graphical Abstract: Keywords: pro-inflammatory cytokines, keratinocytes, fibroblasts, clobetasol propionate, fexofenadine